Palmitate Compromises C6 Astrocytic Cell Viability and Mitochondrial Function - Schmitt, Luisa O. (2024)
Fil: Schmitt, Luisa O. Federal University of Santa Catarina. Laboratory of Neuroimmune-Metabolism, Federal, Brazil.